Development of SAC Media Integrated with Project Based Learning Model on Reaction Rate Material - Azizah Arba Rambe; Ani Sutiani (Universitas Negeri Medan, 2024)
This research aims to determine the analysis of the feasibility level and response of students to SAC (Smart Apps Creator) media integrated with project based learning on reaction rate material. The research method used is Research and Development with a 4D development model approach (define, design, development and disseminate). Research data collection is carried out by interviews and questionnaires or questionnaires that are distributed to teachers and students. This research was conducted at SMAS PAB 8 Saentis. The population and samples in this study are chemistry lecturers, teachers and students of grade XI 2 for the 2023/2024 academic year taken by purposive sampling of 30 people. Based on validity, it shows that the SAC learning media developed was declared valid by validators with the criteria of